1995
DOI: 10.1093/hmg/4.suppl_1.1721
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypertrophic cardiomyopathy: a genetic model of cardiac hypertrophy

Abstract: Familial hypertrophic cardiomyopathy is an autosomal dominant disorder manifesting as cardiac hypertrophy in the absence of increased cardiac work load, which has been studied as a model of myocardial hypertrophy in humans. Hypertrophic cardiomyopathy is genetically heterogeneous with three known disease-genes and two further mapped loci. The disease-genes encode contractile proteins of the thick and thin filaments of the sarcomere: the beta cardiac myosin heavy chain gene on chromosome 14q11, the alpha tropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 0 publications
3
52
0
1
Order By: Relevance
“…These include -cardiac myosin heavy chain (MYH7) (Geisterfer-Lowrance et al 1990;Watkins et al 1992), cardiac myosin-binding protein C (MyBPC-3) (Watkins et al 1995a), cardiac troponin T (TnT2) (Thierfelder et al 1994), Recently, two families were shown to harbor mutations in the light meromyosin domain in the rod region of the protein (Blair et al 2002). The MYH7 mutations account for about 30% of the reported FHC cases (Table 1) (Watkins et al 1995c). To date more than 70 different mutations have been identified in the MYH7 gene (Table 1).…”
Section: Genetic Basis Of Fhcmentioning
confidence: 99%
“…These include -cardiac myosin heavy chain (MYH7) (Geisterfer-Lowrance et al 1990;Watkins et al 1992), cardiac myosin-binding protein C (MyBPC-3) (Watkins et al 1995a), cardiac troponin T (TnT2) (Thierfelder et al 1994), Recently, two families were shown to harbor mutations in the light meromyosin domain in the rod region of the protein (Blair et al 2002). The MYH7 mutations account for about 30% of the reported FHC cases (Table 1) (Watkins et al 1995c). To date more than 70 different mutations have been identified in the MYH7 gene (Table 1).…”
Section: Genetic Basis Of Fhcmentioning
confidence: 99%
“…Mutations in the structural components of muscle are directly responsible for a class of human disease, familial hypertrophic cardiomyopathy (FHC) (Bonne et al, 1998;Seidman and Seidman, 2001;Watkins et al, 1995c). The disease is characterized by cardiac hypertrophy primarily affecting the left ventricle and the intraventricular septum that occurs in the absence of other known conditions leading to hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most of the mutations in the β-MyHC are missense mutations, whereas mutations in the cTnT and myosin-binding protein C genes can be splice-site mutations, deletions of codons, and missense mutations. The disease is also clinically heterogeneous, with some mutant alleles resulting in a poor clinical prognosis, whereas others are associated with a good prognosis (2). In general, mutations in the β-MyHC gene are associated with moderate to severe ventricular hypertrophy and variable sudden death, whereas mutations in cTnT are associated with mild or no hypertrophy and a high incidence of sudden death.…”
Section: Introductionmentioning
confidence: 99%